Foreign Trade in Eastern Europe and the Soviet Union : the Vienna Institute for Comparative Economic Studies Yearbook II. - Friedländer, Michael (Routledge, 2019)
This second yearbook of The Vienna Institute for Comparative Economic Studies presents studies dealing with the economic situation in Eastern Europe and the Soviet Union. Its foreign trade analysis offers insights into the ongoing transition process from centrally planned to market-oriented systems.